Assessment of health professionals’knowledge standardin the municipality of Parakou in 2016. - Gounongbé, Fabien; HINSON, Antoine Vikey; DOVONOU, Albert Comlan; GBANTEHOU, David Yénido; AYÉLO, Paul Gbèmènou; FAYOMI, Benjamain (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Introduction: Health professionals owe themselves to the knowledge of strong medical care that is constantly being revised and updated. The goal of this study is to evaluate the knowledge standard of health professionals in Parakou.Methods: This was a cross-sectional, descriptive and analytical study that lasted three months from May 25th to August 25th, 2016. It focused on Parakou health professionals. Sampling is an exhaustive census. The data are collected using a questionnaire. The standard of knowledge of some diseases was studied, drawing on a CAP study model proposed by Essi and al.Results: The average age of the respondents was 35.4 ± 7.4 years. The majority of participants (39.3%) had a sentant of more than 10 years. Nearly half had good knowledge of the risk factors for hypertension and diabetes. Two out of five were moderately aware of the modes of transmission of viral hepatitis B. 28.4% had a good knowledge of how to detect for cervix cancer. Conclusion: Half of Health professionals ofParakou had a good knowledge of the risk factors for hypertension and diabetes; but less so for modes of transmission of viral hepatitis and cervix cancer detection tests.Key words: Health professionals, knowledge, diseases, Parakou.